Tumor microenvironment-responsive size-switchable drug delivery nanosystems. (4th March 2022) - Hu, Yue; Gao, Shan; Khan, Abdur Rauf; Yang, Xiaoye; Ji, Jianbo; Xi, Yanwei; Zhai, Guangxi
ABSTRACT: Introduction: Compared with ordinary chemotherapeutic drugs, the variable-size nanoparticles (NPs) have better therapeutic effects and fewer side effects. Areas covered: This review mainly summarizes the strategies used to construct smart, size-tunable nanocarriers based on characteristic factors of tumor microenvironment (TME) to dramatically increase the penetration and retention of drugs within tumors. Expert opinion: Nanosystems with changeable sizes based on the TME have been extensively studied in the past decade, and their permeability and retention have been greatly improved, making them a very promising treatment for tumors. Graphical abstract: uf0001